A Review of Influenza Vaccine Immunogenicity and Efficacy in HIV-Infected Adults - Curtis Cooper; Brian Hutton; Dean Fergusson; Edward Mills; Marina B Klein; Guy Boivin; Scott Halperin (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: HIV-seropositive adults are at an increased risk for influenza infection. They also develop more severe influenza disease and are hyporesponsive to current influenza vaccinations.